Simulation based estimation of dynamic mechanical properties for viscoelastic materials used for vocal fold models - Rupitsch, Stefan; Ilg, Jürgen; Sutor, Alexander; Lerch, Reinhard; Döllinger, Michael (Journal of Sound and Vibration, 2011)
In order to obtain a deeper understanding of the human phonation process and the mechanisms generating sound, realistic setups are built up containing artificial vocal folds. Usually, these vocal folds consist of viscoelastic materials (e.g., polyurethane mixtures). Reliable simulation based studies on the setups require the mechanical properties of the utilized viscoelastic materials. The aim of this work is the identification of mechanical material parameters (Young's modulus, Poisson's ratio, and loss factor) for those materials. Therefore, we suggest a low-cost measurement setup, the so-called vibration transmission analyzer (VTA) enabling to analyze the transfer behavior of viscoelastic materials for propagating mechanical waves. With the aid of a mathematical Inverse Method, the material parameters are adjusted in a convenient way so that the simulation results coincide with the measurement results for the transfer behavior. Contrary to other works, we determine frequency dependent functions for the mechanical properties characterizing the viscoelastic material in the frequency range of human speech (100-250 Hz). The results for three different materials clearly show that the Poisson's ratio is close to 0.5 and that the Young's modulus increases with higher frequencies. For a frequency of 400 Hz, the Young's modulus of the investigated viscoelastic materials is approximately 80% higher than for the static case (0 Hz). We verify the identified mechanical properties with experiments on fabricated vocal fold models. Thereby, only small deviations between measurements and simulations occur. (C) 2011 Elsevier Ltd. All rights reserved.